PENERAPAN PERMAINAN CONGKLAK/DAKON UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PADA SISWA KELAS 4 - Nada, Qolbiyah Azkan; Amelasasih, Prianggi (Universitas Tanjungpura, 2024)
This study aims to examine the effectiveness of using the traditional congklak game to improve students' arithmetic skills, particularly multiplication, while incorporating positive reinforcement as a motivational tool. Many elementary school students struggle with understanding abstract mathematical concepts, especially multiplication and division. To address this issue, a series of interventions using the congklak game were conducted. The methodology involved four sessions with a fourth-grade student from MI Al-Hidayah Banjarsari. A pre-test assessed the student